ANALISIS MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) DALAM MENGEMBANGKAN BERPIKIR KRITIS PESERTA DIDIK DI SD NEGERI 1 PRAYA TENGAH - Gazali, Munawir; Januardi, Januardi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This paper discusses the Study of Analysis of Problem Based Learning Models in Developing Students' Critical Thinking at SD Negeri 1 Praya Tengah· and the problems in this research namely; How is the effectiveness of the problem-based learning model (Problem Based Learning) in developing students' critical thinking in natural science subjects at SDN 1 Praya Tengah and what are the supporting and inhibiting factors of problem-based learning models (Problem Based Learning) in developing students' critical thinking at SDN 1 Praya Tengah. This study uses a qualitative approach, data collection techniques through observation interviews and documentation, data analysis techniques used are data reduction, data presentation and conclusion. The results of this study indicate that the effectiveness of the problem-based learning model in developing the critical thinking of students at SDN 1 Praya Tengah has been well implemented. Problem solving in a learning process has an important role to create learning that is liked and liked by students and makes learning more meaningful so that students are able to develop their critical thinking. From the conclusion, the implications are that the learning model is something that educators really need to achieve goals, the school provides training to educators regarding learning models, maintaining what has been done, and for students at SDN 1 Praya Tengah, regarding the ability to think critically through models.